DEVELOPING COMMUNICATIVE SKILLS OF STUDENTS OF HEIS IN CYBER PEDAGOGY (Eureka Journal of Humanities and Social Research, 2026)
In today's rapidly evolving digital landscape, the integration of technology in education has become increasingly prevalent. Higher Education Institutions (HEIs) are continuously exploring innovative approaches to teaching and learning to meet the diverse needs of students and prepare them for the challenges of the 21st century. One such approach gaining momentum is cyberpedagogy, which harnesses digital tools and online platforms to facilitate interactive and engaging learning experiences. In this context, this dissertation seeks to explore the role of cyberpedagogy in enhancing the communicative skills of students in HEIs. By examining the intersection of technology and communication, this study aims to contribute to the growing body of literature on effective pedagogical practices in higher education.
Keywords: Education, learning, Communication, (HEIs), cyberpedagogy, curriculum, skills, psychology, linguistics, constructivism, learning models.